Upgrading seismically isolated bridges with space-flange energy-dissipation devices. Issue 8 (28th August 2021) - Misini, Misin; Ristic, Jelena; Guri, Zijadin; Ristic, Danilo; Pllana, Nebi
Abstract : Non-linear three-dimensional analytical models of bridges with laminated-rubber seismic bearing devices upgraded with multi-directional space-flange energy-dissipation (SF-ED) devices were experimentally validated under multi-directional seismic action by shaking table tests of large-scale prototypes. The experimentally verified hysteretic models were used to model the upgraded seismic isolation (USI) system. The seismic protection benefits of the USI were demonstrated through a comparative analysis of bridge prototypes with both standard and upgraded systems. It was confirmed that the SF-ED devices provided a qualitative contribution under very strong earthquakes in all directions. The variation of the structural characteristics of the devices illustrates the technological options for qualitative seismic upgrading of various types of isolated bridges with complex plane geometries under multi-directional seismic actions.